Pengaruh Likuiditas, Profitabilitas dan Leverage Terhadap Financial Distress - Rizky Nurmala Awaliyah; Barlia Annis Syahzuni (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
This study aims to examine the influence of liquidity, profitability, and leverage on financial distress among companies in the property and real estatee subsector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The independent variables include liquidity, measured by the current ratio (CR); profitability, measured by Return on Assets (ROA); and leverage, assessed using the debt to-equity-ratio (DER). Financial distress, as the dependent variable, is evaluated through the Altman Z-score model. The sample was selected using a purposive sampling method based on specific criteria, resulting in 62 companies and a total of 248 financial statement observations. This research employs a quantitative approach with a causal design and utilizes panel data that combines time series and cross-sectional dimensions. Data analysis was conducted using multiple linear regression, descriptive statistics, and classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, followed by hypothesis testing via SPSS. The findings reveal that both liquidity and profitability have a positive influence on financial distress, whereas leverage exerts a negative effect. The independent variables in this model account for 85% of the variation in financial distress. Accordingly, future studies are encouraged to incorporate additional variables that may also significantly impact a company’s financial distress condition.